Impact Of Nurse Staffing Ratios On Patient Safety In Saudi Hospitals (The Review of Diabetic Studies, 2024)
Introduction and Background: Safe nurse staffing is one of the key factors to deliver high-quality patient care globally. Low nurse-to-patient ratios are consistently associated with an increase in the number of adverse events and in patient deaths. The Saudi Arabian healthcare system is being transformed as a result of the implementation of Vision 2030, which has created an expectation for compliance with stringent quality standards. However, low levels of nursing staff compared to population sizes (approximately 57 nurses/10,000 population) and a heavy reliance on expatriate nursing staff present significant issues to address in relation to the stability of the system and ensuring the safety of patients.Study Objective: The study aims to examine the existing scientific literature from Saudi Arabia regarding the relationship between nurse/patient ratios and patient safety factors including falls, hospital-acquired infections, medication errors and pressure ulcers.Methods: A systematic literature review was performed to synthesise peer-reviewed literature and authoritative policy literature to identify nurse-to-patient (N:P) ratios, emotional exhaustion, missed nursing care, safety culture and nursing turnover rates within Saudi hospitals. The analysis sought to quantify the relationship between staffing proxies and nursing-sensitive safety outcomes for patients in the Kingdom of Saudi Arabia.  Conclusion: The Saudi Arabian healthcare system compromises patient safety because of the shortage of staff available to deliver safe nursing care. To achieve safe, quality nursing practice in Saudi Arabia, policies should address the need for acuity-based nurse-to-patient ratios and provide comprehensive support (financially and professionally) to assist with the retention of nurses.